1995
DOI: 10.1128/iai.63.6.2277-2281.1995
|View full text |Cite
|
Sign up to set email alerts
|

Depressed T-cell proliferation associated with susceptibility to experimental Taenia crassiceps infection

Abstract: Peritoneal infection with Taenia crassiceps cysticerci of naturally resistant (C57BL/10J and C57BL/6J) and susceptible (BALB/cAnN) mice induces a cellular immune depression. T-cell proliferation in response to concanavalin A (ConA) or anti-CD3 was significantly depressed in infected mice of all strains tested. However, in resistant mice, the diminished response to ConA was transient and animals recovered normal responsiveness at day 40, whereas susceptible mice remained suppressed throughout the 40 days of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…On the other hand, several experimental animal studies have attempted to determine the causes of immunosuppression observed in cysticercosis, with different conclusions, such as: release of antigenic products [14] that form circulating immunocomplexes [11], suppressing lymphocyte cytokine production or inducing chromosome instability [15]; increase and/or decrease in CD8+ cells depending on the evolutive phase of the disease [19]; genetic instability and chromosome alterations in circulating lymphocytes induced by infection [20,21]. Furthermore, other investigators have shown that CD4+ T cells (Th1 and/or Th2) and the cytokines produced by these cells are involved in the suppression caused in the experimental model of T. crassiceps [17,22–26].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several experimental animal studies have attempted to determine the causes of immunosuppression observed in cysticercosis, with different conclusions, such as: release of antigenic products [14] that form circulating immunocomplexes [11], suppressing lymphocyte cytokine production or inducing chromosome instability [15]; increase and/or decrease in CD8+ cells depending on the evolutive phase of the disease [19]; genetic instability and chromosome alterations in circulating lymphocytes induced by infection [20,21]. Furthermore, other investigators have shown that CD4+ T cells (Th1 and/or Th2) and the cytokines produced by these cells are involved in the suppression caused in the experimental model of T. crassiceps [17,22–26].…”
Section: Discussionmentioning
confidence: 99%
“…Studies with cestode E/S have demonstrated a similar pattern of proliferative suppression (Rakha et al 1991, Sciutto et al 1995. This led us to question if the generation of a non-specific anti-proliferative host cell is a general phenomenon associated with helminth infection.…”
Section: Discussionmentioning
confidence: 99%
“…These cells may be involved in parasite elimination by cytotoxicity mechanisms. Events of suppression possibly determined by cysticercus antigens have been described in experimental cysticercosis in mice (22).…”
Section: Discussionmentioning
confidence: 99%